Suppression of Autoimmune Arthritis by Small Molecule Inhibitors of the JAK/STAT Pathway - Charles J. Malemud (MDPI AG, 2010)
A skewed ratio of pro-inflammatory to anti-inflammatory cytokines, elevated growth factor synthesis and T- and B-lymphocyte activation are 3 hallmarks of rheumatoid arthritis (RA) pathology. Interleukin-6 (IL-6), IL-7, IL-17, IL-12/IL-23 and growth factors, granulocyte macrophage-colony stimulating factor, IL-3, and erythropoietin activate the Janus Kinase/Signal Transducers and Activators of Transcription (JAK/STAT) pathway. Evidence showed that STAT protein phosphorylation (p-STAT) by activated JAKs is permissive for p-STAT to act as transcription factors by binding to STAT-responsive gene promoter sequences. This event is critical for perpetuating RA, in part, by up-regulating pro-inflammatory cytokine gene transcription. Activation of JAK/STAT by cytokines and growth factors can induce 'cross-talk' with other signaling pathways by which Stress-Activated Protein/Mitogen-Activated Protein Kinase (SAP/MAPK) and Phosphatidylinositide-3-Kinase (PI3K)-mediated signaling are also activated. JAK-specific small molecule inhibitors (SMIs) were developed to test whether JAK/STAT pathway blockade would regulate autoimmune-mediated inflammation. JAK-specific SMI blockade inhibited p-STAT induced by pro-inflammatory cytokines in vitro. Systemically administered JAK-specific SMI blockade also ameliorated biomarkers of inflammation in well-validated arthritis animal models. A few JAK-specific SMIs have made their way into RA clinical trials. In fact, the JAK3-specific SMI, CP-690,500 is the first JAK/STAT SMI to be assessed for clinical efficacy in a Phase III RA trial.